Clinical efficacy of laparoscopic closed hernia ring combined with a patch repair for Gilbert type III indirect inguinal hernia - Binyu, Luo; Qin, Zhang; Xiao, Zhang; Daquan, Zhang; Qing, Guo; Jing, Yu; Yunhong, Tian; Mingyang, Ren (Frontiers in Surgery, 2023)
Purpose: In order to reduce postoperative complications, this study investigated the clinical efficacy of laparoscopic closed hernia ring combined with patch repair for Gilbert type III indirect inguinal hernia. Methods: Through a prospective randomized controlled study, randomly divided into the inner ring close group (85 patients) and the inner ring non-close group (95 patients). . General information such as operative time, postoperative hospital stay and hospital cost were compared between the two groups, and patients were followed up at 1d, 7d, 14d, 21d, 28d, 3 months, 6 months and 12 months after surgery to compare complications such as incidence of seroma, volume of seroma fluid, incidence of pain and VAS pain score. Results: There was no conversion to open procedures in all the patients. the operation time of the closed group was significantly longer than that of the non-closed group , the postoperative closed group was significantly lower than the non-closed group, while we found that the non-closed group had VAS pain score was higher than that of the closed group after surgery according to the statistical results of VSA pain score. The incidence of postoperative seroma and the amount of seroma fluid decreased gradually within the group in both groups, but compared between the two groups, the proportion of cases of seroma in the close group after the operation significantly less than the non-close group. For the comparison of seroma fluid volume between groups, the seroma fluid volume in the non-close group was more than that in the close group after surgery. There were no differences in length of stay, total hospital costs and postoperative complications between the two groups, the postoperative follow-up period was 3-20 months, and no chronic pain or recurrence occurred during the postoperative follow-up period in either group. Conclusions: Closure of the hernia ring is safe and effective for laparoscopic hernia repair for Gilbert type III inguinal hernia, significantly reducing the incidence of postoperative seroma and further reducing postoperative pain without increasing the risk of postoperative infection and recurrence.